2000
DOI: 10.1016/s0733-8635(05)70189-3
|View full text |Cite
|
Sign up to set email alerts
|

Erythroderma

Abstract: Erythroderma can be caused by a variety of underlying dermatoses, infections, and systemic diseases. Many of the findings on history, physical examination, and laboratory evaluation are nondiagnostic. Distinctive clinical and laboratory features pointing to a specific disease may be evident, however. Conclusive clinicopathologic correlation may require multiple and repeated skin biopsies. The prognosis of erythroderma has improved with the advent of innovative dermatologic therapies (e.g., cyclosporine and syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 100 publications
0
12
1
Order By: Relevance
“…As in other studies, the majority of clinical features did not correlate with the etiology [3,5,6,7]. However, in the present study, nail changes were shown to be predictive clinical signs of psoriasis.…”
Section: Discussioncontrasting
confidence: 49%
“…As in other studies, the majority of clinical features did not correlate with the etiology [3,5,6,7]. However, in the present study, nail changes were shown to be predictive clinical signs of psoriasis.…”
Section: Discussioncontrasting
confidence: 49%
“…Most published series reveal that the majority of patients are diagnosed with psoriasis, spongiotic dermatitis, drug reactions or cutaneous T cell lymphoma (CTCL). [67]…”
Section: Etiologymentioning
confidence: 99%
“…[16] Hyperkeratosis, parakeratosis, acanthosis and a chronic perivascular inflammatory infiltrate, with or without eosinophils, are examples. [6] The clinicopathologic correlation is difficult because nonspecific features of erythroderma may mask the specific features of an underlying dermatosis. Direct immunofluorescence studies may be of diagnostic utility in cases of erythroderma secondary to pemphigus foliaceus, bullous pemphigoid, graft-versus-host disease and connective tissue disorders.…”
Section: Histopathologymentioning
confidence: 99%
“…Erythroderma is a rare skin disorder caused by various pathologies, including inflammatory diseases (psoriasis, atopic dermatitis, contact dermatitis, drugs), occult malignancies and cutaneous T-cell lymphomas (CTCL), in which there is a skin-selective recruitment of lymphocytes from the blood [1,2,3]. Sézary syndrome (SS) is a CTCL characterized by erythroderma, peripheral adenopathies and circulating atypical lymphocytes with cerebriform nuclei [4, 5] and is considered a disorder of skin-homing memory Th2 cells.…”
Section: Introductionmentioning
confidence: 99%